STEAM APPROACH IN PRIMARY EDUCATION - kizi, Salokhitdinova Navruza Muradulla; qizi, Axmedova Shokhista Bakhtiyor (PT. Antis International Publisher, 2024)
This article describes the interdisciplinary relationship between technology and natural sciences in primary education based on the STEAM approach. That is, it is explained how technology and natural sciences enter into an integrative process with each other and how the interdisciplinary connection is illuminated based on the STEAM approach. Naturally, there are many technical and technological problems in production, and it is impossible to increase the efficiency of production without eliminating them.